Distribution maps of marine algae from the Iberian Peninsula and the Balearie Islands. XII. Aditions to Focales (Fucopityceae) - Gallardo, Tomás; Pérez-ruzafa, Isabel M. (Botanica Complutensis, 1998)
PÉREZ-RUZAFA. I.M. & GALLARDO, T. 1998. Disíribution maps of marine algaefrom the ¡berian Península and Balearic Islandt Xli? Aditions to Fucales (Fucophyceae). Bol. Complutensis 22: 187-192. New localities for several species of Oída Fecales are indicated. These new sites perform our knowledge about ffie chorology of these species over ffie maps published before in this journal.